2012
DOI: 10.1002/mop.27175
|View full text |Cite
|
Sign up to set email alerts
|

Low‐profile circularly polarized GNSS antenna

Abstract: In this article, we present a low‐profile and low cost antenna for GPS (L1–L2–L5), Galileo (E5–E1–E2), and Glonass (G1–G2) standard. This antenna is a dual‐feed planar patch antenna with four slots to achieve dual‐band operation. The radiating element is fed by a wideband 90° quadrature hybrid coupler to obtain circular polarization on the both bands. The quadrature feeding is achieved using a three‐branch‐line hybrid coupler. The return loss bandwidth of the system (S11 ≤ −10 dB) is 22% in the lower band and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…1. Each antenna generates a right circular polarization (RHCP) [4]- [6] and covers two passbands centered at 1255 and 1575 MHz respectively, with a nominal gain of 20 dB. One can note that the antenna array is very compact for the working frequencies.…”
Section: Specifications and First Resultsmentioning
confidence: 99%
“…1. Each antenna generates a right circular polarization (RHCP) [4]- [6] and covers two passbands centered at 1255 and 1575 MHz respectively, with a nominal gain of 20 dB. One can note that the antenna array is very compact for the working frequencies.…”
Section: Specifications and First Resultsmentioning
confidence: 99%
“…The excellent performances of the antenna are mainly due to the shorted annular stacked patch structure and four ports proximity-coupled probe-fed feeding mechanisms. Axial ratio and gain characteristics at low elevation are better than the other structures designed for GPS or GNSS application [8][9][10][11][12][13][14], which are compared in Table 2. The simulated and measured RHCP gain of the antenna at different frequencies are presented in Figure 12, and it is observed that the stable gain bandwidth can be obtained for gain > 2.5 dBi in the GNSS bands.…”
Section: Resultsmentioning
confidence: 99%
“…There are mainly three methods to achieve broadband performance of microstrip antennas, they are using two or more radiating structures which work at different but contiguous resonant frequencies [4,5], using coupling feeding scheme [6] and adding external matching circuits [7]. Several multi-band or wideband lowprofile antennas have been designed in the literature [8][9][10][11][12] for GPS or GNSS application. However, few of them can obtain broad beam width and good axial ratio at low elevation, which are useful to suppressing multipath interferences.…”
Section: Introductionmentioning
confidence: 99%
“…2 and Fig. 3, which is based on the study and the development seen in [3], [13] and [14], respectively. The concept behind this design was studied by many researchers, such as A. Heidari [15] and W. Liao [16], who produced two microstrip GPS antennas in rectangular and circular form with slots on the edges in order to enable dual band operation.…”
Section: The Antenna Design's Theory and Descriptionmentioning
confidence: 99%